Perlindungan Hukum Terhadap Satwa Terancam Punah Di Indonesia : Bagaimana Ikan Air Tawar Endemik Bangka Belitung - bunga; winanda Kusuma; Ave Agave Situmorang (UNIB Press, 2023)
The purpose of this study is to analyze forms of protection for rare and endangered species. Moreover, to find out the mechanism for determining the protection of rare and endangered animals. The research method was carried out normatively with a statutory and conceptual approach. The results show that Indonesia already has several laws protecting animals, especially aquatic biodata. The protection is in the form of full protection and limited protection. Unfortunately, the endemic freshwater fish of Bangka Belitung has not received protection status in Indonesian laws and regulations. Furthermore, the determination of fish species protection status is carried out through a. initiative proposals, b. verification of proposals, c. public consultation, d. policy analysis, e. scientific recommendations, and f. determination of fish species protection status. Moreover, the Minister of Maritime Affairs and Fisheries assigns a status category to the type of protection. Local governments are also given the authority to determine limited protection